The impacts of remuneration on employee retention and job satisfaction among private higher education institutions' lecturers / Yen Ping Ki , Kiat Sing Heng and Celeste Jee Wee Lau - Yen, Ping Ki; Kiat, Sing Heng; Wee Lau, Celeste Jee (Universiti Teknologi MARA Cawangan Sarawak, 2022)
This research investigated the remuneration's impacts on employee retention and job satisfaction among Private Higher Education Institutions' lecturers in Sarawak, Malaysia during the Covid-19 pandemic. A theoretical model with Remuneration, Employee Retention, and Job Satisfaction was proposed, with a significant effect on Remuneration Satisfaction among institutions' academic employees. Using Microsoft Form, this study surveyed two hundred and five academic employees from nine institutions. The findings revealed a significant relationship between Remuneration and Job Satisfaction and a significant relationship between Employee Retention and Job Satisfaction. However, there is no significant relationship between Remuneration and Employee Retention.